Hashtags as Digital Mobilisation: A Corpus-Assisted Discourse Analysis of #IndonesiaGelap - Novi Eka Susilowati; Nadia Khumairo Ma'shumah; Arina Isti'anah (Masyarakat Linguistik Indonesia Universitas Andalas, 2026)
Protest discourse has become a fruitful source of data for critical studies, as reflected in the Indonesian socio-political landscape in early 2025. As social media plays an important role in disseminating information and shaping public discourse, narratives and hashtags related to the protests quickly gained widespread attention and became trending topics on social media. This study investigates how digital activism is represented through the #IndonesiaGelap “Dark Indonesia” hashtag on X. This study adopted a corpus-assisted discourse approach to analyse 16,103 posts through the analytical framework of Theo van Leeuwen’s Social Actor Theory. The quantitative and qualitative analyses demonstrate that Indonesian citizens use the hashtag to express their rejection, criticism, mobilisation, and solidarity by involving particular social actors. Therefore, netizens used proper names referring to political elites to represent the most dominant social actors, which serves as a discursive strategy to blame the worsening political situation in Indonesia. In addition, the corpus reveals that many users associated those events with previous presidential elections, which they perceived as being controlled by political dynasties, with the metaphor of “dark” reinforcing these negative evaluations. These findings indicate that hashtags functioned to construct the ideological distinction between “us”, represented by citizens, and “them”, represented by the Indonesian government, elites, and media. This study emphasises the function of hashtags in shaping online political dissent and democratic debate.